การพัฒนากระบวนการจำหน่ายผู้ป่วยในหอผู้ป่วยอายุรกรรมชาย 1 โรงพยาบาลนครพิงค์ จังหวัดเชียงใหม่ - อังคณา คำห้าง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Continuous improvement of the work process will provide effective services to consumers. The purpose of this developmental study was to develop a patient discharge process in Male Medical Ward 1, Nakornping Hospital, Chiang Mai Province, using the Lean Concept of Womack and Jones (2003). The study population consisted of 27 staff members working in the ward. The research instruments included: 1) a table describing the service process activities, 2) a value analysis form, 3) a process flow chart, 4) a time spent on activities record form, and 5) focus group interview guidelines regarding problems, obstacles and recommendations for improving the service process. These research instruments were validated by three experts. The interrater reliability of four observers for the time recording was 1.0. The data were analyzed by using descriptive statistics. The results were as follows: 1. The new patient discharge process in the Male Medical Ward 1 consisted of 6 major activities and 16 minor activities which was a reduction of 1 major activity and 9 minor activities from the previous development process. 2. The standard time of the new patient discharge process took 72.26 minutes which was a reduction of 242.57 minutes from the previous development process. 3. Problems and obstacles relating to the development of a patient discharge process could be classified into 3 dimensions: 1) Management: this included indefinite policy and planning for improving the work process using the Lean Concept, a lack of responsible persons available for monitoring the process, and inadequate resources to carry out the process; 2) Implementation: this included the discontinuities of the developmental process because of the high workload, and communication difficulties among personnel due to the rotating of the work shift; and 3) Personnel: this included personnel’s knowledge of the application of Lean Concept and their familiarity with the routine patient discharge process. The recommendations comprised of the development of a plan for work process improvement, the assignment of responsible persons, the support of resources, the management of staffing to match the workload, and the provision of training regarding Lean Concept for personnel. The results of this study indicated that the development of a patient discharge process using Lean Concept can decrease the activities and time spent on the process while maintaining the quality of service. Therefore, administrators can apply the result of this study as guidelines for improving the quality of services in other departments of the organization.